Ascites permagna caused by large mesenteric cyst in 2 years old male: A case report - I Made Yullyantara Saputra; Putu Gde Karyana; Sanjaya Putra; Metriani Nesa; Made Dharmajaya; Kadek Deddy Arianta (DiscoverSys Inc., 2019)
Background: Mesenteric cysts are documented as a rare entity in the pediatric population. They are considered as benign intraabdominal tumors with an unknown etiology and may occur anywhere in the mesentery of the gastrointestinal tract from the duodenum to the rectum. They are most commonly located in the mesentery of the ileum followed by localization in the sigmoid mesocolon. Approximately one-third of mesenteric cysts occur in children younger than 15 years of age and are slightly more common in males. The surgery is the common methods to remove the cyst.Case presentation: A 2-year-old boy was hospitalized with a history of the bloated abdomen and dull achy pain on the left side of the abdomen since I year before admitted. Physical examination revealed distended of abdomen and ascites. Laboratory investigation showed normal limit; ultrasonography investigation showed cystic lesion and fluid collection in the cavum abdomen. It was confirmed with a CT scan. We diagnosed the patient with ascites permagna et causa suspected mesenteric cyst. After the diagnosis, a laparoscopic exploration and drainage ascites and total resection of the cyst were performed. Seven days after surgery, the patient was in good condition and discharged from the hospital — no distention in the abdomen.Conclusion: The mesenteric cyst can be the cause of ascites and can be well treated with laparoscopic modalities; the outcome is excellent with no malignancy founded.